1991
DOI: 10.1507/endocrj1954.38.541
|View full text |Cite
|
Sign up to set email alerts
|

Placental Lactogen Secretion during Prolonged-Pregnancy in the Rat: The Ovary Plays a Pivotal Role in the Control of Placental Function.

Abstract: The serum of rats at mid-pregnancy contains at least 2 distinct placental lactogen (PL)-like substances tentatively termed placental lactogen-alpha (PL-alpha) and placental lactogen-beta (PL-beta) (Endocrinol Japon 38: 533-540, 1991). We have investigated the secretory patterns of three placental lactogens (PL-alpha, PL-beta and placental lactogen-II) during normal pregnancy and in two prolonged-pregnancy models. Pregnancy was prolonged by the introduction of new corpora lutea by inducing ovulation on day 15 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Previously, we reported that there were at least two distinct PL-like substances in mid-pregnant rat serum, PL-I and PL-a (molecular masses of 45-50 and 55-60 kDa respectively) [14,15], although the structure of PL-a has not been determined. PL-a was recognized preferentially by antiserum All-86, which was specific to the hydrophilic region of PL-II, and the recognition site of the PL-a core protein appeared to be analogous to PL-II rather than to PL-I [28].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previously, we reported that there were at least two distinct PL-like substances in mid-pregnant rat serum, PL-I and PL-a (molecular masses of 45-50 and 55-60 kDa respectively) [14,15], although the structure of PL-a has not been determined. PL-a was recognized preferentially by antiserum All-86, which was specific to the hydrophilic region of PL-II, and the recognition site of the PL-a core protein appeared to be analogous to PL-II rather than to PL-I [28].…”
Section: Discussionmentioning
confidence: 98%
“…The PRL surges following mating, which is induced by cervical stimulation, is necessary to initiate and maintain the progesterone secretion function of the corpus luteum. PL is a primary candidate for the luteotrophic factor of gestation, in view of the observations that PRL secretion ceases at mid-pregnancy following the initiation of PL secretion [33] and PLs are able to bind to the ovarian PRL receptor [14,15,28]. Mid-pregnancy-specific PLs appear to be peculiar to the rat, mouse and hamster [7,17], while PL expression occurs predominantly during late pregnancy in other species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The member of the placental PRL family has been assumed to be one of the luteotropic factors during pregnancy after placentation [13]. In accord with this concept, the mid-pregnancy-specific PLs are secreted again in late pregnancy and are associated with the prolonged secretion of progesterone from the corpora lutea beyond the normal pregnancy period in the prolonged pregnancy model, which is developed by induction of a new set of corpora lutea following successive treatment with PMSG and hCG at mid-pregnancy [1,27]. The present study clearly demonstrated that recPL-Im has luteotropic activity in a primary culture of luteal cells of pregnant rat.…”
Section: Discussionmentioning
confidence: 99%